2012
DOI: 10.1111/cid.12004
|View full text |Cite
|
Sign up to set email alerts
|

Is Mandibular Reconstruction Using Vascularized Fibula Flaps and Dental Implants a Reasonable Treatment?

Abstract: This study showed that the use of dental implants in patients with fibula flaps is an appropriate and successful option for dental rehabilitation, even in those with risk factors such as smoking, alcohol use, and irradiation. Implant placement in irradiated grafted bone seems to be a high-risk procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…Twenty‐seven studies informed of the death occurrences among the patients during the follow‐up. Eighteen studies had patients who were also submitted to adjunctive chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐seven studies informed of the death occurrences among the patients during the follow‐up. Eighteen studies had patients who were also submitted to adjunctive chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 studies, all patients were submitted to chemotherapy. Part of the patients in 9 studies were smokers, and 2 studies excluded smokers . It was informed in 5 studies that some of the patients were frequent consumers of alcoholic beverages.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 328 studies were included for full-text assessment, of which 277 were excluded for one of the following reasons: (1) studies focusing on irrelevant outcome assessment (n = 144), such as bone loss or primary stability; (2) studies without a non-risk group (n = 56); (3) studies only providing patient-related data (n = 21); (4) studies where data related to implant failure could not be calculated (n = 53); and (5) studies where the reported data were represented in another included in our analysis (n = 3) [19][21]. As a result, 51 studies met the inclusion criteria for meta-analysis, with 33 studies for smoking [22]–[54], 16 for radiotherapy [31], [44], [55]–[68], five for diabetes [31], [44], [47], [48], [69] and four for osteoporosis [44], [70][72], respectively. Of note, four studies involved more than one risk factor and were included in more than one group [31], [44], [47], [48].…”
Section: Resultsmentioning
confidence: 99%
“…This also applies to transfer tissue that undergoes postoperative irradiation in the mouth. Jacobsen et al (Jacobsen et al, 2014) recorded an Implant survival rates of 86% in non-irradiated grafted fibular bone, and 38% in irradiated grafted fibular bone.…”
Section: General Factors Influencing the Wound Healing In The Mouthmentioning
confidence: 99%